2018
DOI: 10.18203/2320-6012.ijrms20184433
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pneumococcal vaccine in patients with chronic obstructive pulmonary disease (COPD)

Abstract: Background: Pneumococcal infections are frequent cause chronic obstructive pulmonary disease (COPD) exacerbations and though various guidelines recommend the use of pneumococcal vaccines routinely to COPD patients to prevent exacerbations, the data regarding the effectiveness of this vaccine is limited and contradictory. Aims and objectives was to compare the frequency of exacerbations in patients of COPD before and after administration of pneumococcal vaccine and to find out the frequency of exacerbations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…While these may be the best outcomes to look at from a vaccine efficacy point of view, clinically relevant outcomes for COPD patients would be exacerbation rates. A randomised, non-placebo controlled trial, however, showed decreased exacerbation rate in COPD patients after administration of a pneumococcal polyvalent vaccine [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While these may be the best outcomes to look at from a vaccine efficacy point of view, clinically relevant outcomes for COPD patients would be exacerbation rates. A randomised, non-placebo controlled trial, however, showed decreased exacerbation rate in COPD patients after administration of a pneumococcal polyvalent vaccine [ 17 ].…”
Section: Introductionmentioning
confidence: 99%